2001
DOI: 10.4049/jimmunol.167.1.302
|View full text |Cite
|
Sign up to set email alerts
|

A NF-κB/Sp1 Region Is Essential for Chromatin Remodeling and Correct Transcription of a Human Granulocyte- Macrophage Colony-Stimulating Factor Transgene

Abstract: The GM-CSF gene is expressed following activation of T cells. The proximal promoter and an upstream enhancer have previously been characterized using transfection and reporter assays in T cell lines in culture. A 10.5-kb transgene containing the entire human GM-CSF gene has also been shown to display inducible, position-independent, copy number-dependent transcription in mouse splenocytes. To determine the role of individual promoter elements in transgene function, mutations were introduced into the proximal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 53 publications
2
30
0
1
Order By: Relevance
“…A complex signaling network regulates the expression of inducible GM-CSF [24,25]. In L. pneumophila-infected lung epithelial cells, we noted a TLR2 and TLR5 dependent activation of PKC.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A complex signaling network regulates the expression of inducible GM-CSF [24,25]. In L. pneumophila-infected lung epithelial cells, we noted a TLR2 and TLR5 dependent activation of PKC.…”
Section: Discussionmentioning
confidence: 83%
“…Activation of the transcription factors NF-kB and AP-1 is considered to significantly contribute to GM-CSF expression [24,25]. We therefore demonstrated that L. pneumophila induced GM-CSF was controlled by NF-kB and AP-1 (c-Jun).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Response elements that were not found by sequence analysis in the 1.4-kb 5'-region of the TP gene included AP1, NF-kB, HIF1 and Egr1. In addition to their individual roles in regulating transcription, reports suggest that there is cross-talk between transcription factors, including evidence that gene activation by Sp1 can be modulated by positive and negative interactions with other transcription factors (Hirano et al, 1998;Krehan et al, 2000;Cakouros et al, 2001). Experiments with constructs containing 5'-truncations of the TP promoter revealed that the transcriptional activity dramatically decreased with deletion of sequence spanning 7368 to 7155 and 7155 to 764.…”
Section: Discussionmentioning
confidence: 99%
“…NF-B has previously been shown to enhance DNA accessibility around the NF-B-RE to which it binds. For example, at the granulocyte-macrophage colonystimulating factor gene (GM-CSF) promoter, NF-B causes increase in chromatin accessibility via remodeling through recruitment of the ATPase component of the SWI/SNF chromatin remodeling complex, BRG1 (4,22). More recently, constitutive activation of NF-B along with AP1 has been associated with increased accessibility of the IL-6 promoter in highly invasive breast cancer cells (40).…”
Section: Discussionmentioning
confidence: 99%